ポーラカスプ ノ エンジリョクセン エンジリョク デンバ ト ワクセイ カン クウカン ジバ ノ カンケイ b. デンバ ト デンリュウ ケイ ダイ1カイ キョクイキ ニオケル デンリケン ジキケン ソウゴウ カンソク シンポジウム PART 1 - 藤井, 良一; フジイ, リョウイチ; 飯島, 健; イイジマ, タケシ; FUJII, Ryoichi; IIJIMA, Takesi (国立極地研究所, 1979)
P(論文) 最近,カスプ領域のfield-aligned currentの研究が行われだした.しかし,何をもってカスプfield-aligned currentと呼ぶのか,また,経度方向にどういう分布をしているのか等の諸特性はまだ分かっていない.この論文では,カスプfield-aligned currentの分布および惑星間空間磁場B_yによる分布のシフトおよびB_zとカスプfield-aligned currentの強度との相関を調べた.その結果,1)カスプ型field-aligned currentは,午前側と午後側のregion 1の境目か午前側や午後側に移動することでは説明できない.2)カスプ型field-aligned currentの午前側と午後側タイプの境目は,IMF B_yにコントロールされる.3)カスプ型field-aligned current強度とIMF B_zとは,B_zが負の値のとき負でかつ線型の相関がある. From the analysis of vector magnetometer data of more than 200 passes of TRIAD that were recorded at McMurdo, Antarctica, during the winter season, 1974, the principal characteristics of the cusp field-aligned currents (FAC) in the midday south polar region are determined: 1) Cusp type FAC's exist in the midday polar region that is separate from the region 1 (and 2) FAC regimes. No satisfactory explanation is obtained by attributing the cusp type FAC's to dislocation in latitude and or shift in longitude of the general distribution of the region 1 and 2 FAC's. 2) The demarcation line between the pre-noon type and the post-noon type cusp FAC's is controlled well by the polarity of IMF B_y. 3) There is a linear correlation between the intensity of the cusp FAC and the negative IMF B_z component. No clear relation was found between the cusp FAC intensity and the positive IMF B_z component. departmental bulletin paper